(untitled) (Jurnal Teknologi (Sciences & Engineering), 2020)
Lack of work focusing on deformation mechanism has been undertaken in the Late Tertiary sequence during Late Neogene time at the Renah Gajah Mati I region in Bengkulu basin. The present study was aimed at reconstructing tectonic deformation occurring within the basin during the Late Neogene, employing balancing and restoring techniques, kinematic and dynamic analyses. The Late Neogene deformation was mainly controlled by compression, which has resulted in folding and thrusting. Hence, the rock sections underwent shortening that varied from 1.42-1.83 km or 0.75%-0.78% with the estimated rate of deformation 0.12-0.15 mm/year. Two types of tectonic structures developed within the region, fault propagation folds and trishear faults. The brittle deformation extended sequentially in the direction of tectonic transport, resulting in a series of faults. The generated faults constitute imbricate fans with a relatively closely-spaced thrust system. The array of thrusts is apparently associated with folds that strike NW-SE, implying the geometry of fault-linked folding. The hanging wall anticlines are generally asymmetric overturned folds, indicating a shallow ramping fault with a high shear pattern. In regional context, the general strike of structures within the study area appears relatively parallel to the NW-SE trending Barisan orogen. This feature suggests that tectonic transport responsible for structuring was likely at the NE- SW direction.